2011
DOI: 10.1097/ccm.0b013e31822571ce
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of albumin therapy in acute lung injury measured by proton nuclear magnetic resonance spectroscopy of plasma: A pilot study*

Abstract: Objectives Improved means to monitor and guide interventions could be useful in the intensive care unit (ICU). Metabolomic analysis with bioinformatics is used to understand mechanisms and identify biomarkers of disease development and progression. This pilot study evaluated plasma 1H-NMR spectroscopy as a means to monitor metabolism following albumin administration in acute lung injury (ALI) patients. Design This study was conducted on plasma samples from 6 albumin-treated and 6 saline-treated patients from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…This study showed that blood albumin levels normalized and oxygenation improved with albumin treatment compared to saline treatment. In this study, 1 H-NMR spectroscopy was introduced to characterize systemic metabolic responses and identify patients’ unique response to pharmacologic therapy and appealed to play a potential role in the guiding treatment and reducing healthcare cost [68]. …”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This study showed that blood albumin levels normalized and oxygenation improved with albumin treatment compared to saline treatment. In this study, 1 H-NMR spectroscopy was introduced to characterize systemic metabolic responses and identify patients’ unique response to pharmacologic therapy and appealed to play a potential role in the guiding treatment and reducing healthcare cost [68]. …”
Section: Reviewmentioning
confidence: 99%
“…Although the amplification of quantitative metabolomics in clinic bioinformaticsis in its infancy, it has been increasingly used recently. It is a unique tool of discovery because it identifies multiple endogenous markers, and it changes over time which can be predictive of clinical outcome and therapeutic response [67,68]. The ability of magnetic resonance imaging (MRI) and metabolic NMR were investigated to detect and quantify inflammationmediated lung injury [69].…”
Section: Metabolomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, most of the studies relied on using sodium trimethylsilyl [2,2,3,3- 2 H 4 ] propionate (TSP) as an internal standard, whereas 2,2,3,3-d 4 -3-(trimethylsilyl) propionic acid (TMSP) or 4,4-dimethyl-4-silapentane-1-sulfonic acid (DSS) were only used in a few studies. Other chemical compounds, such as tetramethylsilane (TMS) or calcium formate, were rarely used [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, gene co-expression in circulating leukocytes was dependent upon plasma metabolites, showing networks linkage with lipoproteins, lipids and amino acids. Stringer et al (86) showed that quantitative metabolomics was potentially useful in sepsis-induced acute lung injury, and Park et al (70) showed a progressive trajectory of the principal component analysis (PCA) of plasma metabolites in albumin-treated patients toward a normal healthy metabolic profile. The most discriminatory regions by PCA consisted of parts of the spectra in which amino acids, glucose and other metabolites are present, suggesting utility to evaluate nutritional imbalance of critical illness and to assess recovery from critical illness (70).…”
Section: Bioinformatics and Computational Sciencesmentioning
confidence: 99%